Gambaran Proses Putus Cinta pada Wanita Dewasa Muda di Jakarta: Sebuah Studi Kasus - Rumondor, Pingkan C. B. (Bina Nusantara University, 2013)
The end of an intimate relationship is a common incident in pre-marital young adult relationship. Hence, there are only a few literatures that explain this phenomenon. Therefore, this article is made to explain the definition, effect, individual differences and theoretical model explaining relationship dissolution, especially in young adult woman ini Indonesia. Theoretical review is used to analyze one case of young adult woman in Jakarta seeking for professional help in a Psychology Clinic. Method used to analyze data is qualitative, phenomenology with Interpretative Phenomenological Analysis (IPA) technique. Data are gathered with semi structured, open-ended and non-directive questions. The result of this study is the respondent going through the process of